Effect of age on directional microphone hearing aid benefit and preference. - Wu Y (Journal of the American Academy of Audiology, 2010)
Background: Despite the recognition that the directional microphone hearing aid (DMHA) is an important intervention aimed at helping older hearing-impaired adults understand speech in noisy environments, there is little evidence that older listeners can actually benefit from directional processing. Purpose: The objective of this study was to determine if older and younger adults can obtain and perceive comparable benefit afforded by DMHAs. Study Sample: Twenty-four hearing-impaired adults aged 36 through 79 yr were fit with switchablemicrophone hearing aids and tested in the laboratory and the field. Data Collection and Analysis: In the laboratory, the listeners' directional benefit and preferences for microphonemodes (directional vs. omnidirectional) were assessed using various speech-recognition-in-noise tests. In the four-week field trial, a paired-comparison technique and paper-and-pencil journals were used to determine the benefit provided by directional processing. The effects of age on directional benefit/preference were analyzed using generalized linear models with controlling for the effect of hearing loss. Results: The results revealed that age did not have a significant effect on directional benefit and preference as measured in the laboratory. However, the field data showed that older age was significantly associated with a lower preference for the directional mode. Conclusion: These results indicate that although listeners of different ages may obtain and perceive comparable benefit from DMHAs in laboratory testing, older users tend to perceive less benefit than do younger users in the real world. The implications of these findings are discussed.